Effect of Cyclic Martensitic γ-ε-γ Transformations on Diffusion Characteristics of Carbon in an Iron–Manganese Alloy - Bondar, V.Y.; Danilchenko, V.E.; Mazanko, V.F.; Filatov, O.V.; Iakovlev, V.E. (Успехи физики металлов, 2018)
Carbon-diffusion characteristics in metastable Г18C2 iron–manganese alloy after the cyclic γ-ε-γ (f.c.c.–h.c.p.–f.c.c.) martensitic transitions were investigated using the radioactive-isotope method. As shown, the process of carbon transport acceleration in the alloy phase-hardened by means of the γ-ε-γ transformations was caused by two independent mechanisms.